Acute toxicity of Corexit EC9500A and assessment of dioctyl sulfosuccinate as an indicator for monitoring four oil dispersants applied to diluted bitumen. (15th February 2018) - MacInnis, Ceara Y.; Brunswick, Pamela; Park, Grace H.; Buday, Craig; Schroeder, Grant; Fieldhouse, Ben; Brown, Carl E.; van Aggelen, Graham; Shang, Dayue
Abstract: The present study investigated oil dispersant toxicity to fish species typical of the cooler regions of Canada, together with less well‐documented issues pertaining to oil dispersant monitoring. The oil dispersant toxicity of Corexit EC9500A was assessed for the freshwater fish species rainbow trout and the seawater species coho, chinook, and chum, with a final median lethal concentration (LC50) acute lethality range between 35.3 and 59.8 mg/L. The LC50 range was calculated using confirmed 0‐h dispersant concentrations that were justified by fish mortality within the first 24 h of exposure and by variability of the dispersant indicator dioctyl sulfosuccinate (DOSS) used to monitor concentrations at later time points. To investigate DOSS as an oil dispersant indicator in the environment, microcosm systems were prepared containing Corexit EC9500A, Finasol OSR52, Slickgone NS, and Slickgone EW dispersants together with diluted bitumen. The DOSS indicator recovery was found to be stable for up to 13 d at 5 °C, 8 d at 10 °C, but significantly less than 8 d at ≥15 °C. After 3 d at temperatures ≥15 °C, the DOSS indicator recovery became less accurate and was dependent on multiple environmental factors including temperature, microbial activity, and aeration, with potential for loss of solvents and stabilizers. A final assessment determined DOSS to be a discrepant indicator for long‐term monitoring of oil dispersant in seawater. Environ Toxicol Chem 2018;37:1309–1319. © 2018 SETAC